Oxidative Stress Biomarkers in the Equine Erythrocyte Suspension After In Vitro Incubation with Leaf Extract Obtained from Rhododendron myrtifolium Schott & Kotschy (Ericaceae) - Prokopiv, Andriy; Tkachenko, Halyna; Honcharenko, Vitaliy; Kurhaluk, Natalia; Nachychko, Viktor; Sosnovsky, Yevhen; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
A noteworthy European member of the genus is Rhododendron myrtifolium Schott & Kotschy, an evergreen clump-forming dwarf shrub up to 50 cm in height, occurring in high-mountain habitats of the eastern and southern Carpathian Mountains and northern Balkans, largely within altitudes of 1400–2500 m. It has been shown that R. myrtifolium possesses antibacterial and antiviral effects of their extracts, while the biochemical features and bioactive potentials of R. myrtifolium remain unexplored. In the current study crude aqueous extract from the leaves of R. myrtifolium was assessed for antioxidant activities, cytotoxicity, and anti-hemolytic potential. The aim of this study was to assess possible antioxidant and anti-hemolytic effects of an extract derived from R. myrtifolium leaves using oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS) as biomarker of lipid peroxidation, aldehydic and ketonic derivatives of oxidatively modified proteins, the total antioxidant capacity (TAC)] and HCl-induced hemolysis assay on equine erythrocytes’ model. Our results demonstrated that the treatment by extract obtained from leaves of R. myrtifolium in dose 5 mg/mL decreased the TBARS level in the equine erythrocytes’ suspension, while aldehydic and ketonic derivatives of oxidatively modified proteins and total antioxidant capacity increased. These changes were statistically non-significant. When R. myrtifolium extract was added to the erythrocyte suspension, the maximum level of hemolysis has occurred after 6.0 min of incubation with 0,1M HCl. The total duration of hemolysis after R. myrtifolium extract incubation was 10.5 min compared to 12 min in the control sample. The results showed that HCl-induced hemolysis was increased by the treatment of R. myrtifolium extract. On the other hand, no changes in the size and shape of cells, as well as protuberances on their surfaces and/or cells, after exposure to R. myrtifolium extract was observed. Importantly, no ruffled edges (echinocyte or crenated cells) were noted. The erythrocytes maintained the normal biconcave shape, except a very few cells, underwent a slight change in conformation. Therefore, extract obtained from the leaves of R. myrtifolium in dose 5 mg/mL Interestingly, when assayed for its cytotoxic evaluation against equine erythrocytes, the extract obtained from leaves of R. myrtifolium in dose 5 mg/mL showed mild hemolytic activity, while the oxidative stress biomarkers were non-significantly changed. Our results further suggest that Rhododendron myrtifolium could be further investigated for the isolation and purification of the active constituents.